المختص النفساني العيادي كمرافق حياة مدرسية لطفل يعاني من اضطراب التوحد - حمادنّ,أمينة; عشاشرة,أسماء (University of Eloued جامعة الوادي, 2025)
تبرز الدراسة الحالية دور المختص النفساني العيادي في الوسط المدرسي كمرافق حياة مدرسية لطفل التوحد بولاية بلعباس نموذجا، حيث تعرض الدراسة حالة طفل توحد مدمج في الوسط المدرسي بالطور الابتدائي مع المرافقة المدرسية لمدة سنتين، من خلال عرض وصفي لنتائج تقييم اختبار CARS لشدة التوحد والتواصل والتفاعل الاجتماعي، بالإضافة إلى عرض نتائج تحصيله الدراسي من خلال تحليل لمحتوى الدفتر المدرسي الخاص بالتلميذ وكل ذلك في فترتين: قبل حضور مرافقة الحياة المدرسية، ثم بعد تدخل مرافقة الحياة المدرسية. أظهرت النتائج تحسنا ملحوظا سواء في شدة التوحد للطفل أو في مختلف جوانب النمو كالتواصل والتفاعل الاجتماعي كما شهد التلميذ تحسنا في تحصليه الدراسي بعد تدخل مرافقة الحياة المدرسية. أما عن تحليل محتوى الدفتر المدرسي للتلميذ فقد أقرت المعلمات تكيف التلميذ مع العملية التعليمية وتحسن سلوك التلميذ بناءا على ملاحظات الأساتذة ومديرة المدرسة وولي الأمر.The current study highlights the role of the clinical psychologist in the school environment as a support for the school life of a child with autism, using a case from the state of Bel-Abbes as a model. The study presents the case of an integrated autistic child in a primary school setting, receiving school support for two years. It describes the results of the CARS assessment regarding the severity of autism, communication, and social interaction, in addition to analyzing the child's academic performance based on the content of their school notebook. This was examined in two phases: before the school support intervention and after its implementation. The results indicated significant improvements in both the child's autism severity and various areas of development, such as communication and social interaction. The student also showed better academic performance following the intervention. As for the analysis of the student's school notebook, teachers confirmed the child’s adaptation to the educational process and noted improvements in behavior, as observed by the teachers, the school principal, and the parent.
تجربة ميدانية بمدرسة ابتدائية بولاية سيدي بلعباس
Keywords: المختص النفساني العيادي; مرافق الحياة المدرسية; طفل التوحد; clinical psychologist; support for the school life; child with autism; elementary school; the state of Bel-Abbes